Perheet 1995 - (:unkn) unknown (Tilastokeskus, 1996)
Väestölaskenta 1995
Familjer 1995
Families 1995
Keywords: tilastot; väestötilastot; perheet; lapsiperheet; Väestö; Väestörakenne ja väestönmuutokset